2022
DOI: 10.1038/s42003-022-03630-3
|View full text |Cite
|
Sign up to set email alerts
|

A panel of nanobodies recognizing conserved hidden clefts of all SARS-CoV-2 spike variants including Omicron

Abstract: We are amid the historic coronavirus infectious disease 2019 (COVID-19) pandemic. Imbalances in the accessibility of vaccines, medicines, and diagnostics among countries, regions, and populations, and those in war crises, have been problematic. Nanobodies are small, stable, customizable, and inexpensive to produce. Herein, we present a panel of nanobodies that can detect the spike proteins of five SARS-CoV-2 variants of concern (VOCs) including Omicron. Here we show via ELISA, lateral flow, kinetic, flow cytom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 106 publications
1
28
0
Order By: Relevance
“…Nanobodies targeting SARS-CoV-2 spike protein were selected as previously described 12 , 13 . Genes of N-terminally PelB (MKYLLPTAAAGLLLLAAQPAMA)-tagged tandem homotrimer of the nanobody connected with two (GGGGS) 4 linkers and C-terminally 6×His-tagged were synthesized and subcloned in the pMES4 vector.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanobodies targeting SARS-CoV-2 spike protein were selected as previously described 12 , 13 . Genes of N-terminally PelB (MKYLLPTAAAGLLLLAAQPAMA)-tagged tandem homotrimer of the nanobody connected with two (GGGGS) 4 linkers and C-terminally 6×His-tagged were synthesized and subcloned in the pMES4 vector.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that two nanobodies, P17 and P86, potently neutralize SARS-CoV-2 VOCs including Alpha/B.1.1.7, Beta/B.1.351, Gamma/P.1, Delta/B.1.617.2, and Omicron/BA.1/BA.2 12 , 13 . We also determined the epitopes recognized by these nanobodies (P17 and P86) using Cryo-EM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homology models of NIBIC-71 and 7G7/κ Fabs were generated by SWISS-MODEL 32 . The atomic model of S protein 26 and the homology models of the Fabs were manually fitted into the density by using UCSF Chimera 33 and Coot 34 . Figures were prepared by using ChimeraX 35 and PyMOL (Schrödinger, LLC).…”
Section: Methodsmentioning
confidence: 99%
“…The anti-SARS-CoV-2 monoclonal antibodies demonstrated positive effects in pre-exposure prophylaxis against susceptible variants ( 24 ), prevention of progression to severe COVID-19 ( 25 ), and reduction of patient mortality ( 26 ). In addition, because it can recognize the receptor binding domain (RBD) or other SARS-CoV-2 receptors, nanobodies have also been developed to detect the spike proteins of SARS-CoV-2 variants including Omicron ( 27 ), and show the potential of neutralizing SARS-CoV-2 variants ( 28 31 ).…”
Section: Introductionmentioning
confidence: 99%